NEW OPPORTUNITIES FOR THE FORMATION OF ABILITIES FOR THE PERCEPTION AND PRESENTATION OF NON-STANDARD IDEAS IN THE TEACHING OF STUDENTS (Intent Research Scientific Journal, 2023)
This article will talk about the new possibilities of the formation of the ability to perceive and present non-standard ideas in the teaching of students. The author, relying on pedagogical data and written sources, studied the existing specific aspects of the formation of the ability to perceive and present non-standard ideas in the teaching of students on the basis of existing scientific literature.